A Soft 3D Acoustic Metafluid with Dual‐Band Negative Refractive Index. Issue 9 (15th December 2015) - Raffy, Simon; Mascaro, Benoit; Brunet, Thomas; Mondain‐Monval, Olivier; Leng, Jacques
Abstract : Spherical silica xerogels are efficient acoustic Mie resonators. When these sub‐wavelength inclusions are dispersed in a matrix, the final metafluid may display a negative acoustic refractive index upon a set of precise constraints concerning material properties, concentration, size, and dispersity of the inclusions. Because xerogels may sustain both pressure and shear waves, several bands with negative index can be tailored.